Factors Related to Violence Against Children in Families in Kebayakan District, Central Aceh Regency in 2022 - Hasritawati; Barirah Madeni; Sri Wahyuni MS (HM Publisher, 2022)
Background: There have been 3,087 cases of violence against children, including 852 physical violence, 768 psychological, and 1,848 cases of sexual violence. This figure is quite high. In Central Aceh, in 2019, there were 20 cases of violence against children, while in 2020, there were 22 cases of violence against children consisting of physical, sexual, and psychological violence to child neglect. This study aims to determine the factors associated with violence against children in the family of Kebayakan District, Central Aceh Regency. Methods: The research design was analytically observational with a cross-sectional approach. A total of 62 subjects participated in this study, where the subjects were mothers with children aged 6-15 years. Data analysis was carried out univariate and bivariate in order to determine the factors that play a role in child abuse. Results: There is no relationship between family income (p-value = 0.272 (p> 0.05), there is a relationship between the mother's education (p-value = 0.033 (p <0.05), and there is no relationship between mother's psychological state (p-value = 0.465 (p>0.05) with violence against children in the family Conclusion: A mother’s education is a factor associated with violence against children in the family.